Elektronische Entscheidungsunterstützung zur Annäherung an eine sichere Arzneimitteltherapie - Haefeli, Walter E.; Seidling, Hanna (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Because of its inherent complexity, it is a considerable challenge to tailor drug treatment to a prevalent disease and its subgroups, which are increasingly defined by genomic variability (personalized medicine) and require consideration of context information such as co-morbidity, co-medication, patient preferences, and the specific characteristics of the healthcare sector. Thus, optimum treatment decisions might not be taken intuitively any longer, because decisions must be made both rapidly and increasingly based on analyses of complex relations of numerous variables that exceed the processing performance of a human brain. Hence, computer support is indispensable to ensure error-free high-performance medicine. A key step in computer-supported medication safety is to implement a computerized physician order entry (CPOE) system that compiles a patient’s medication in a structured and coded format enabling the link to clinical decision support (CDS) systems. Implementing a CPOE is hence a strategic step for a hospital, which is crucial to exhaustingly and consistently prevent medication errors. Thereby, the best performance of a CPOE is achieved if it is deeply integrated into an electronic patient record thus enabling access to relevant patient information, which again has to be structured to allow processing. To efficiently support drug treatment, CDS systems must fulfill high-quality standards with regard to underlying data, integration, and user-interaction to ensure that they support but do not impede the provision of care.
Gesehen am 19.08.2019